Who Are the Compliant Correctional Clients? New Evidence on Protective Factors among Federal Supervised Releases. (October 2021) - DeLisi, Matt; Drury, Alan; Elbert, Michael
Protective factors facilitate success on community supervision, but relatively little is known about correctional clients who are highly compliant particularly in the federal system. Drawing on a near population of federal clients on supervised release in the Midwestern United States, the current study examined variables associated with compliant supervision status. One day on supervision contributed to a 1% reduction in the logged odds of supervision compliance. Clients with no drug history had 793% increased odds, clients with sustained remission had 620% increased odds, and clients with early remission had 458% increased odds of compliant supervision status relative to clients actively using drugs. Among the federal Post Conviction Risk Assessment (PCRA) indices, only PCRA Criminal History was significant as clients with less extensive criminal history were more likely to be compliant supervision clients. A one-unit change in PCRA Criminal History status was associated with 25% reduced odds of supervision compliance. Total conditions were inversely associated with compliant supervision status with each additional condition associated with a 19% reduced likelihood of compliant supervision status. None of the demographic variables was significantly associated with compliant supervision status. Implications of the findings for the protective factor paradigm in corrections are discussed.